Enhanced Steering and Drive Adaptations of Modified Ride-On Toy Cars for Improved Directional Control in Very Young Children With Severe Multiple Developmental Impairments - Aceros, Juan; Lundy, Mary (Frontiers in Pediatrics, 2020)
Background and Purpose: One emerging power mobility device (PMD) option that has gained recognition as a means for a cost-effective introduction to power mobility for young children is the battery powered modified ride-on toy car. Many groups, nationally and internationally, have been modifying battery powered ride-on toy cars by adding seating support and a large center placed push button switch for motor activation. The purpose of this technical report is to introduce an enhanced steering and drive system based on proportional control through a joystick. Key Points: This report offers 1) a technical description of these modifications that allow directional steering and programmable starting and driving velocity, 2) an example of a modified ride on toy, including common seating modifications, and 3) a short summary of results from a group of 7 children under the age of six with complex, severe disabilities. Clinical Impact: Although proportional joystick modifications are more complex than the common single switch activation, they allow children greater control to achieve self-initiated, self-directed movement that allow play, peer interaction, and exploration in their natural environments, even in the most highly complex cases.